Comparison of Time Lapse Embryo Morphokinetics Monitoring and Conventional Pronuclear Morphology Assessment to Determine Embryo Quality in Endometriosis Patients - Muharam, R.; Ikhsan, Muhammad; Setiyawan, Wisnu; Emeraldi, Malvin; Wiweko, Budi (KnE Medicine, 2016)
Objective Endometriosis patients who underwent IVF program has poorer embryo quality, leads to low successive rate. In order to determine embryo quality, time lapse embryo monitoring and pronuclear (PN) morphology assessment were used to predict and select the most promising embryo. This research is expected to exhibit comparison the use of both methods in endometriosis patients in order to implement the most effective evaluation in future embryo implantation prognosis. Methods This cohort research was conducted to 72 embryos from 19 endometriosis patients who underwent IVF program in Yasmin Reproductive Clinic, Cipto Mangunkusumo Hospital. After ICSI was performed two-nucleated embryo later be monitored by its cleavage time and would be classified into categories for good quality embryo and other classes were considered poor quality embryo for time lapse monitoring. Then from time lapse monitoring, PN morphology were assessed regarding pronuclear scoring. Results Based on 72 embryos observation, we found that there was no significant difference between good and poor quality embryo based on PN scoring with p=0.185, and also between time-lapse morphokinetic monitoring and embryo quality with p=0.526. However, we found that there was a weak correlation between PN scoring and embryo quality with p=0.049 and r=0.233. Conclusion There was no significant difference found between time lapse monitoring and PN scoring in endometriosis patients in order to determine embryo quality. However, there was a weak correlation between PN scoring and embryo quality. This might be due to small number of samples taken and visual bias during observation.